1998
DOI: 10.1088/0953-8984/10/21/017
|View full text |Cite
|
Sign up to set email alerts
|

Role of the pseudogap in the electron transport of quasicrystals and their approximants

Abstract: There are two routes in the opening of the pseudogap: one due to the band separation in a disordered system such as expanded liquid mercury and amorphous alloys and the other due to the Fermi surface-Brillouin zone interaction in quasicrystals and their approximants. The role of the pseudogap in the electron transport has been studied by plotting resistivities at 4.2 and 300 K against the electronic specific heat coefficient for a total of 49 quasicrystals and their approximants on the log-log diagram in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…The pseudogap arises because of the Fermi surface-Brillouin zone interaction, and it has been shown that the transport properties are dependent on the depth of the gap. 4 Consequently, there is considerable interest in clarifying the relative importance of quasiperiodic order and the complex chemistry of quasicrystals in determining the width and depth of the pseudogap.…”
mentioning
confidence: 99%
“…The pseudogap arises because of the Fermi surface-Brillouin zone interaction, and it has been shown that the transport properties are dependent on the depth of the gap. 4 Consequently, there is considerable interest in clarifying the relative importance of quasiperiodic order and the complex chemistry of quasicrystals in determining the width and depth of the pseudogap.…”
mentioning
confidence: 99%
“…Eq (3) and this result thus suggest that in addition to the decrease of ξ into the insulator, there is a contribution to the increase of T o from a slow decrease of N(ε F ). Independent evidence for such a decrease of N(ε F ) is obtained from the observation for quasicrystals that N(ε F ) from the specific heat decreases as the slowly decreasing 1/ ρ(295K) into the insulator [12,13]. In the latter of these references this correlation included also i-AlPdRe.…”
Section: Results For T O and ξ ξ ξ ξmentioning
confidence: 97%
“…The resistivity of crystallized alloys may be further increased by the strong Fermi level-Brillouin zone interaction which flattens electronic bands. This flattening of electronic bands further lowers the minimum in electronic density of states, increases effective mass and lowers the Fermi velocity v F [28,29].…”
Section: For Comparison Inmentioning
confidence: 99%